Optical Conceptual Design for the Giant Magellan Telescope Multi-Object Astronomical and Cosmological Spectrograph - Ribeiro, Rafael Alves de Souza (2020)
This thesis is being submitted to the area of optical astronomical instrumentation applied to Extreme Large Telescopes (ELTs). It presents the development of the conceptual design for the optics of the Giant Magellan Telescope Multi-object Astronomical and Cosmological Spectrograph (GMACS) for the period 2015 to 2020. ELTs will be the next generation of telescopes, scheduled for the end of the 2020s or early in the following decade. Together with the James Webb Space Telescope (JWST) and major Survey Telescopes, such as the Vera C. Rubin Observatory, they will provide the scientific community with a set of instruments which will have unprecedented capabilities for application in many areas of astronomy, such as studies of the formation and evolution of planetary systems, galaxy assembly and evolution, exoplanets characterizations, and first light and reionization exploration. The Giant Magellan Telescope (GMT) will be the first ELT in operation, and it is planned for commissioning in the late 2020s. GMT is a Gregorian optical telescope with a collecting area of 368 m² and is currently under construction in north-northeast of La Serena, Chile, at the Las Campanas Observatory. As part of the GMT first light instruments, a wide-field optical Multi-Object Spectrograph (MOS) with a moderate resolution is foreseen to be essential to satisfying the diverse GMT scientific goals. This research is based on the optical activities for the conceptual development of this instrument, GMACS, a general-purpose wide-field spectrograph for GMT. These activities consisted of: (i) a conceptual review of low to medium resolution Volume Phase Holographic (VPH) grating optical spectrographs for ELTs, from the perspective of the optical design; (ii) a review of pre-existing MOS with similar GMACS specifications to correlate the design solutions adopted with their technical requirements and design challenges; (iii) a detailed description of the methodology and tools developed for the conceptual optical design, modeling, and analysis; (iv) the results, presented in the conceptual design review held in September, 2019, based on the 2016 project de-scope requested by the GMTO through its Statement of Work and attachments (GMT-SOW-01091); and (v) the conclusions and the descriptions of the future stages of the optical project. The proposed GMACS optical concept is a multi-object, two-channel, VPH transmission grating optical spectrograph with spectral coverage spanning from 320 nm to 1,000 nm, the highest practical throughput over the entire spectral range (including the deep UV-Blue 320 nm to 350 nm), a wide-field of approximately 7.5 in diameter, spectral resolving powers from 500 to 6,000 and resolutions from approximately 8.5 Å to 0.7 Å for a 0.7 slit width baseline. The optical design is composed of a 2,200 mm f/8.2 refractive split collimator (270 mm diameter exit pupil) and two 594 mm f/2.2 refractive cameras optimized for the 320 nm to 600 nm and 550 nm to 1,000 nm spectral ranges, resulting in the current largest étendue for a single optical MOS. As part of the optomechanical performance results, we emphasize the solution found for mechanical deformations generated by the variation of the gravity vector of the current GMACS structure that affect the spectral stability and the image quality. The methodology developed in this research for the integration of finite element analysis and the Zemax optical design software revealed that two synchronized active compensators for each of the GMACS channels (one located in the collimator group, for focusing, and the other in the camera group, for fine focusing) could satisfactorily compensate these effects and meet the image stabilization requirements. In conclusion, the research results were crucial to direct the development of other GMACS engineering areas and decisive for the success of the instrument.